Keselarasan Manusia dan Alam dalam Kearifan Lokal Jawa dan Batak sebagai Pembentukan Spiritualitas Ekologis Generasi Z - Arum Kusniati; Hadiahta Siregar (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the local wisdom values of the Javanese and Batak ethnic groups in maintaining harmony between humans and nature, as well as their relevance to shaping the spirituality of Generation Z. The research method used is descriptive qualitative with a library research approach. Data were obtained from books, scientific articles, and previous studies. The findings show that Memayu Hayuning Bawana and Habonaron Do Bona both emphasize balance and harmony among humans, nature, and God. These values can be applied by Generation Z to develop ecological spirituality rooted in local wisdom and aligned with modern challenges. This study contributes to strengthening the spiritual identity of young generations in the digital era through the revitalization of local wisdom values, The younger generation can find a more holistic and harmonious life guide, while strengthening their spiritual identity amidst the currents of globalization and digitalization. This research contributes to efforts to shape the character and spirituality of an environmentally conscious young generation, based on local wisdom.